Samoodločanje otrok in mladostnikov s posebnimi potrebami v izobraževanju - Licardo, Marta; Schmidt, Majda (Revija za elementarno izobraževanje, 2014)
Self-Determination of Children and Youth with Special Needs in Education. In the article we briefly present the development of self-determination from various perspectives. The focus is on a functional model of self-determination, which has increasingly been applied in the field of special education and rehabilitation. Research in the area of self-determination contributes to the understanding of topic dimensions and raises ideas of development in practice. Much foreign research highlights the benefits of the functional model, in which self-determination is a skill that can be learned by learning about choice, decision making, problem solving, planning and reaching goals, self-observing, self-evaluating, self-reinforcement, selfawareness, and knowing oneself (Wehmeyer, 1999). In Slovenia self-determination is less known, and we can mostly find it in special education and the rehabilitation of persons with intellectual disabilities in terms of self advocacy, autonomy development, empowerment, etc. We emphasise that systematic development and teaching of self-determination skills can contribute to better performance in various areas of special needs education: for example in vocational education where there is quite a large population of students with special needs who can easily end up being socially excluded, and experience school failure and unemployment. The model is also useful in the work with parents of children with special needs at all levels of education and in the field of teacher education.
Keywords: self-determination; special education needs; autonomy; empowerment; self-realization